Anti‐seasonal flooding drives substantial alterations in riparian plant diversity and niche characteristics in a unique hydro‐fluctuation zone - Ye Liu; Xiaodie Duan; Xiaoling Li; Wenxiong Yi; Gong Chen; Jin Yang; Danli Deng; Xiaojuan Guo; Zhengjian Yang; Guiyun Huang; Meixiang Hu; Chen Ye (Ecology and Evolution)
Abstract Human‐induced disturbances such as dam construction and regulation have led to widespread alterations in hydrological processes and thus substantially influence plant characteristics in the hydro‐fluctuation zones (HFZs). To reveal utilization of limited resources and mechanisms of inter‐specific competition and species co‐existence of plant communities based on niche breadth and overlap under the different HFZs of the Three Gorges Reservoir (TGR) in China, we conducted a field investigation with 368 quadrats on the effects of hydrological alterations on plant diversity and niche characteristics. The results showed anti‐seasonal flooding precipitated the gradual disappearance of the original diverse niches, resulting in the reduction of plant species richness and functional diversity and more obvious competition among plant species with similar resource requirements. Annuals, perennials and shrubs accounted for 71.23%, 27.39% and 1.37%, respectively, suggesting that annuals and flood‐tolerant riparian herbs were favored under such novel flooding conditions. A consistent increase in species number, Shannon‐Wiener diversity index and Simpson dominance index with altitude was inconsistent with hump‐shaped diversity–disturbance relationship of the intermediate disturbance hypothesis, while the opposite trend was observed for the Pielou evenness index. This species distribution pattern might be caused by several synergetic attributes (e.g., the submergence depth, plant tolerant capacity to flooding, life form, dispersal mode and inter‐specific competition). Vegetation types shifted from xerophytes to mesophytes and eventually to hygrophytes with the increasing flooding time in the HFZs. Hydrological alterations proved to be the paramount driver of vegetation distribution in the different HFZs. The niche analysis provided the first insights on the mechanisms of resource utilization and inter‐specific competition, of which annuals could germinate quickly after soil drainage to achieve the greatest competitive advantages and occupy a larger niche space than other plants. Vegetation was still in the early stage of primary succession in the novel riparian forests. Therefore, vegetation restoration strategies should be biased towards herbaceous plants, due to annuals with better environmental adaptability, supplemented by shrubs and small trees. To establish a complete reference system for vegetation restoration, natural vegetation monitory plots in the different succession stages should be established in the different HFZs of the TGR, and their environmental conditions, community structures and inter‐specific relationships further analyzed.